A Λ-shaped donor–π–acceptor–π–donor molecule with AIEE and CIEE activity and sequential logic gate behaviour1. Issue 28 (28th July 2015) - Mei, Xiaofei; Wen, Guixiu; Wang, Jingwei; Yao, Huimei; Zhao, Yan; Lin, Zhenghuan; Ling, Qidan
<x xml:space="preserve">Abstract</x> A novel Λ-shaped donor–π–acceptor–π–donor molecule BCPMM with AIEE, CIEE and polymorphism-dependent fluorescence properties was utilized to construct five simple logic gates and more than ten kinds of sequential combinational logic systems.